Bacillus velezensis Rc218 as a biocontrol agent against Fusarium head blight of wheat: revealing genome insights and metabolite profile production - Palazzini, Juan Manuel (2021)
Bacillus velezensis RC218 was originally isolated from wheat anthers as a potential antagonist of Fusarium graminearum sensu stricto, the causal agent of Fusarium head blight (FHB) in Argentina. We demonstrated the ability of B. velezensis RC218 to reduce disease severity and DON accumulation in vitro, under greenhouse and field trials. The current presentation extends characterizing B. velezensis RC218 by genome sequencing and secondary metabolite production. Secondary metabolite clusters wereidentified with antiSMASH3.0 or direct blasting. Culture supernatants containing secondary metabolites were analyzed by LC-MS. The field study demonstrated that B. velezensis RC 218 could reduce FHB severity and the associated mycotoxin (deoxynivalenol) production to undetectable levels. The genome sequencing allowed us to accurately determine the taxonomy of the strain using a phylogenomic approach, which places it in the B. velezensis clade. The genome mining allowed us to identify 9 active secondary metabolites conserved by all B. velezensis strains and one additional secondary metabolite, the lantibioticericin, which is unique to this strain. This represents the first confirmed production of ericin by a B. velezensis strain. Biocontrol activity can be related to the production of several lipopeptides, from the surfactin, fengycin and iturin families. Microbiome analysis also demonstrated that application of the bioicontrol on spikes does not impactnative populations dynamics.